Determination of trace cadmium in seawater using combination of polystyrene coated magnetic nanoparticles based DSPE and triethylamine assisted Mg(OH)2 method - Kocoglu, Elif Seda; Kublay, Irem Zehra; Gosterisli, Tugce Unutkan; Bakirdere, Sezgin (ELSEVIER, 2022)
Precise and accurate determination of elements in seawater requires efficient analytical approaches that are able to overcome challenges such as high salt content and the very low concentrations of elements. In the present study, the triethylamine (TEA) assisted Mg(OH)2 co-precipitation method was applied to seawater prior to the preconcentration of cadmium by an optimized polystyrene coated magnetic nanoparticles based dispersive solid phase extraction (PS-MNP-DSPE) method. The enriched analyte was determined by a flame atomic absorption spectrometer, which was fitted with a slotted quartz tube as an absorbance signal booster. The limit of detection (LOD) and limit of quantification (LOQ) values calculated for cadmium under optimum conditions of the PSMNP-DSPE-SQT-FAAS method were 0.23 and 0.77 mu g kg- 1, respectively. Seawater sampled from the coast of West Antarctica was used to verify the accuracy and applicability of proposed method, and the recovery results (97 - 106%) obtained were very satisfactory.
Keywords: Cadmium; FAAS; Mg(OH) (2); TEA; MNP-DSPE; Seawater; PLASMA-MASS SPECTROMETRY; ATOMIC-ABSORPTION-SPECTROMETRY; SOLID-PHASE EXTRACTION; RARE-EARTH-ELEMENTS; SIMULTANEOUS SEPARATION; ULTRATRACE LEVELS; WATER SAMPLES; PRECONCENTRATION; METALS; TUBE; Chemistry